A Lumped Particle Modeling Framework for Simulating Particle Transport in Fluids (Communications in Computational Physics, 2010)
This paper presents a lumped particle model for simulating a large numberof particles. The lumped particle model is a flexible framework in modeling particleflows, embodying fundamental features that are intrinsic in particle laden flow, includingadvection, diffusion and dispersion. In this paper, the particles obey a simplified version of the Bassinet-Boussinesq-Oseen equation for a single spherical particle.However, instead of tracking the individual dynamics of each particle, a weighted spatialaveraging procedure is used where the external forces are applied to a “lump” ofparticles, from which an average position and velocity is derived. The temporal evolutionof the particles is computed by partitioning the lumped particle into smallerentities, which are then transported throughout the physical domain. These smallerentities recombine into new particle lumps at their target destinations. For particlesprone to the effects of Brownian motion or similar phenomena, a symmetric spreadingof the particles is included as well. Numerical experiments show that the lumpedparticle model reproduces the effects of Brownian diffusion and uniform particle transportby a fluid and gravity. The late time scale diffusive nature of particle motion isalso reproduced.